Photocurable composition, cured product thereof and coated article

Through the photocurable composition with a specific ratio, the problem that the low viscosity photocurable coating in the prior art is difficult to achieve transparency and wear resistance, and a low viscosity and high performance cured film suitable for various coating methods is achieved.

CN119585328APending Publication Date: 2025-03-07SHIN ETSU CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380053877.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-25
Filing Date
2023-06-27
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

While maintaining a low viscosity, it is difficult to achieve excellent transparency and wear resistance. Especially in the solvent-free state, the composition is prone to thickening, which limits the coating method used.

Method used

By combining surface-modified inorganic particles, difunctional (meth)acrylate, trifunctional (meth)acrylate and photoradical initiator in a specific proportion, a photocurable composition that is basically solvent-free and low viscosity is formed to achieve a cured film that has both transparency and wear resistance.

Benefits of technology

The formation of a low viscosity photocurable composition is achieved, and can be applied to coating methods such as spray coating and flow coating, and has a low impact on environmental load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585328A_ABST
    Figure CN119585328A_ABST
Patent Text Reader

Abstract

Provided is a photocurable composition containing: (A) 1-30 parts by mass of surface-modified inorganic particles which are obtained by chemically bonding an organosilicon compound represented by formula (1) and at least one of a hydrolysate and a condensate thereof with respect to 100 parts by mass of inorganic particles, and which have a median diameter in a volume-based particle size distribution of 1-60 nm; (B) a bifunctional (meth) acrylate; the present invention relates to a photocurable resin composition which is characterized in that the amount of component (A) is 10-35 mass%, and the total amount of component (A), component (B) and component (C) is 70 mass% or more, and to a method for producing the photocurable resin composition, said photocurable resin composition being characterized in that the amount of component (A) contained therein is 10-35 mass%, and the amount of component (B) contained therein is 70 mass% or more. (In the formula, R1 is a hydrogen atom or the like, R2 is an alkylene group, R3 is an alkyl group or the like, R4 is an alkoxy group or the like, and n is an integer of 1-3. > # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photocurable composition, a cured product thereof, and a coated article, and more particularly to a photocurable composition which forms a cured product having low viscosity and excellent abrasion resistance, a cured product thereof, and a coated article. Background Art

[0002] Photocurable coating compositions are widely used for coating transparent plastic materials because they have a short curing time and can be cured at low temperatures. Plastic materials have lower surface hardness than glass and are easily damaged. Therefore, the photocurable coating films used are required to have high transparency and abrasion resistance.

[0003] Furthermore, in recent years, from the viewpoint of protecting the natural environment and simplifying the production process, there has been a demand for the development of solvent-free photocurable coating compositions that do not require a solvent drying process and do not release volatile organic solvents into the atmosphere.

[0004] However, for example, in order to exert excellent atmospheric curability and wear resistance of the cured film, a large amount of high-viscosity multifunctional (meth) acrylic acid compounds need to be introduced into (meth) acrylic acid compositions, and the coating composition thickens significantly. High-viscosity coatings are not suitable for coating methods such as spraying and flow coating, which greatly limits the coating methods that can be used. Therefore, in recent years, there is a need for solvent-free photocurable coating compositions that have low viscosity and excellent atmospheric curability and form a cured film with wear resistance.

[0005] Patent Documents 1 to 3 propose adding inorganic particles to a photocurable coating composition as a method for improving the wear resistance of a coating film. In particular, it is reported that the dispersibility in the coating and the wear resistance of the cured film are improved when the surface of the inorganic particles is treated with an organic compound.

[0006] However, these photocurable coating compositions contain an organic solvent and become highly viscous compositions in a solvent-free state.

[0007] Patent Documents 4 and 5 report solvent-free photocurable coating compositions containing surface-treated silica. However, the use of silica results in a high viscosity of the composition and the transparency of the resulting coating film is insufficient.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2017-132975

[0011] Patent Document 2: Japanese Patent No. 6189547

[0012] Patent Document 3: Japanese Patent Application Publication No. 2008-150484

[0013] Patent Document 4: Japanese Patent Application Publication No. 2010-189620

[0014] Patent Document 5: Japanese Patent Application Publication No. 2020-012078 Summary of the invention

[0015] Problems to be solved by the invention

[0016] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a low-viscosity photocurable composition containing substantially no solvent and forming a cured film having both transparency and abrasion resistance, and a cured product thereof and a coated article.

[0017] Means for solving problems

[0018] The present inventors have conducted intensive research to achieve the above-mentioned object, and as a result, have found that a photocurable composition that is substantially solvent-free and low-viscosity and forms a cured film having both transparency and abrasion resistance is obtained by mixing surface-modified inorganic particles whose surfaces are modified with a predetermined organosilicon compound having a (meth)acryloyl group, a difunctional (meth)acrylate, a trifunctional (meth)acrylate, and a photoradical initiator in a specific ratio, thereby completing the present invention. It should be noted that in the present invention, the term "substantially" means that the solvent contained in the composition is less than 10% by mass.

[0019] That is, the present invention provides:

[0020] 1. A photocurable composition comprising:

[0021] (A) 1 to 30 parts by mass of surface-modified inorganic particles, which are chemically bonded to at least one of an organosilicon compound represented by the following formula (1), a hydrolyzate thereof and a condensate thereof, and have a volume-based median diameter of 1 to 60 nm, based on 100 parts by mass of the inorganic particles;

[0022] (B) difunctional (meth)acrylate,

[0023] (C) trifunctional (meth)acrylate and

[0024] (D) a photoradical initiator,

[0025] The amount of the component (A) is 10 to 35% by mass, and the total amount of the components (A), (B) and (C) is 70% by mass or more.

[0026] [Chemistry 1]

[0027]

[0028] In the formula, R 1 is a hydrogen atom or a methyl group, R 2 is an alkylene group having 1 to 20 carbon atoms, R 3 are each independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 4 Each is independently a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, or a halogen atom, and n is an integer of 1 to 3;

[0029] 2. The photocurable composition according to 1, wherein the inorganic particles are silica particles;

[0030] 3. The photocurable composition according to 2, wherein the value of D90 / D10 in the volume-based particle size distribution of the surface-modified inorganic particles is 3.2 or less;

[0031] 4. The photocurable composition according to 2 or 3, wherein the surface-modified inorganic particles are 29 The peak area (Q) of -105 to -130 ppm in the Si-NMR spectrum 4 ) to the ratio of the peak area (Q) between -80 and -130 ppm (Q 4 Particles obtained by surface modification of sol-gel silica particles having a surface area of ​​0.8 or less;

[0032] 5. The photocurable composition according to any one of 1 to 4, wherein the surface-modified inorganic particles are particles to which one or more selected from the group consisting of a silane compound represented by the following formula (5) and a disilazane compound represented by the following formula (6) are further chemically bonded,

[0033] R 5 3SiY(5)

[0034] R 5 3Si-NH-SiR 5 3(6)

[0035] In the formula, R 5 Each is independently an alkyl group having 1 to 8 carbon atoms, and each Y is independently a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, an acyloxy group having 1 to 6 carbon atoms, an amino group, or a halogen atom;

[0036] 6. The photocurable composition according to any one of 1 to 5, wherein the content of the volatile organic solvent relative to the entire composition is less than 10% by mass;

[0037] 7. The photocurable composition according to any one of 1 to 6, wherein the kinematic viscosity at 25° C. is 100 mm 2 / s or less;

[0038] 8. A cured product formed by curing the photocurable composition according to any one of 1 to 7.

[0039] 9. An article coated with the cured product according to 8.

[0040] Effects of the Invention

[0041] According to the present invention, a solvent-free photocurable composition can be obtained which has low viscosity and forms a cured product having both excellent transparency and abrasion resistance. Therefore, the photocurable composition of the present invention can be applied to a coating method suitable for low-viscosity coatings such as spray coating and flow coating, and can be used as a hard coating coating with low environmental load because it contains substantially no solvent. DETAILED DESCRIPTION

[0042] The present invention will be described in detail below. It should be noted that in the present invention, "(meth)acryloyl" means "acryloyl" or "methacryloyl".

[0043] [Photocurable composition]

[0044] The photocurable composition of the present invention contains the following (A) to (D) components.

[0045] (A) Surface modified inorganic particles

[0046] (B) Difunctional (meth)acrylate

[0047] (C) Trifunctional (meth)acrylate

[0048] (D) Photoradical initiator

[0049] <(A) Surface-modified inorganic particles>

[0050] The component (A) is surface-modified inorganic particles in which at least one of an organosilicon compound represented by the following formula (1), a (partial) hydrolyzate thereof and a condensate thereof is chemically bonded in an amount of 1 to 30 parts by mass per 100 parts by mass of the inorganic particles and in which the median diameter in the volume-based particle size distribution is 1 to 60 nm.

[0051] The dispersibility of the inorganic particles in the photocurable composition can be improved by (partially) hydrolyzing the organosilicon compound represented by the following formula (1) to form a silanol compound, and using the silanol compound to treat inorganic particles to undergo a dehydration condensation reaction with the hydroxyl groups on the surface of the inorganic particles, or by using the above-mentioned compound without hydrolyzing it and allowing the alkoxy group of the above-mentioned compound to undergo a dealcoholization condensation reaction with the hydroxyl groups on the surface of the inorganic particles to modify the surface of the inorganic particles.

[0052] [Chemistry 2]

[0053]

[0054] (Where R 1 is a hydrogen atom or a methyl group, R 2 is an alkylene group having 1 to 20 carbon atoms, R 3 are each independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 4 Each is independently a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, or a halogen atom, and n is an integer of 1 to 3.

[0055] (1) Inorganic particles

[0056] The elements constituting the inorganic particles used in the present invention are not particularly limited, and examples thereof include Group 13 elements, Group 14 elements (excluding carbon), first series transition elements, second series transition elements, third series transition elements, and lanthanoid elements.

[0057] As the particles of the Group 13 element, oxide particles derived from aluminum, boron, indium, or the like are particularly preferred.

[0058] As the particles of the Group 14 element (excluding carbon), metal silicon particles and oxide particles derived from silicon, tin, or the like are preferred.

[0059] As the particles of the first series transition element, oxide particles derived from titanium, manganese, zinc, etc. are preferred. These oxides are often used as light absorbing materials of specific wavelengths.

[0060] As the particles of the second series transition element, silver particles, oxide particles derived from yttrium, zirconium, etc. are preferred. These oxides are often used as light absorbing and fluorescent materials of a specific wavelength.

[0061] As the particles of the third series transition element, gold particles, oxide particles derived from hafnium, tantalum, etc. are preferred.

[0062] As the particles of lanthanoid elements, oxide particles derived from lanthanum, cerium, praseodymium, neodymium, terbium, dysprosium, ytterbium or the like are preferred.

[0063] These metal oxides may be used alone or in combination of two or more thereof. The term "combined" has a broad meaning and includes both simple mixing and compounding via chemical bonding.

[0064] The composite via chemical bonding refers to a form represented by the following general formula (8).

[0065] (M 1 O x ) d (M 2 O y ) e (8)

[0066] Among them, M1 Any one represented by the element symbol of Al, B, In, Si, Ge, Sn, Ti, Mn, Zn, Y, Zr, Hf, Ta, La, Ce, Pr, Nd, Tb, Dy, or Yb. 2 Any one represented by the element symbol of Al, B, In, Si, Ge, Sn, Ti, Mn, Zn, Y, Zr, Hf, Ta, La, Ce, Pr, Nd, Tb, Dy, Yb, which is the same as M 1 The elements selected in are not the same elements. For x and y, if M 1 The valence of is set to a, which can be expressed as x = a / 2. If M 2 The valence of is set to b, then it can be expressed as y = b / 2. d and e are real numbers satisfying d + e = 1, and satisfying 0 < d < 1 and 0 < e < 1. That is, in the structure, M 1 and M 2 Units bonded via oxygen.

[0067] M 1 With M 2 It can be dispersed or concentrated in the structure. 1 and M 2 The structure dispersed in the structure can be seen in the co-hydrolyzates of various metal alkoxides. 1 and M 2 The structure with partial structure is seen in core-shell composite particles (particles having metal oxide fine particles as cores and another metal oxide shell outside the core), and is formed, for example, by stepwise hydrolysis of multiple types of metal alkoxides.

[0068] The inorganic particles may be core-shell composite particles having a single or a composite of the above-mentioned metal element or metal oxide as a core and a shell of a single or a composite of the above-mentioned metal element oxide on the outside of the core. Examples of such core-shell composite particles include core-shell composite particles having a titanium oxide-tin oxide composite oxide (titanium oxide particles in which tin is solid-dissolved) as a core and a shell of silicon oxide on the outside of the core.

[0069] As specific examples of the inorganic particles used in the present invention, particles of silicon dioxide, aluminum oxide, titanium oxide, zinc oxide, cerium oxide, tin oxide, boron oxide, indium oxide, etc. can be cited. When a dispersion of these particles is added to, for example, a coating, generally more than one inorganic particle is used according to the purpose, so it does not prevent the dispersion in the present invention from containing a variety of inorganic particles. Among the above-mentioned inorganic particles, silicon dioxide particles are preferred from the perspective of dispersibility in the composition and ease of obtaining.

[0070] When silica particles are used as inorganic particles, in the volume-based particle size distribution obtained by the dynamic light scattering method, the particle size that accumulates to 10% by volume from the side with the smaller particle size is set as D10, and the particle size that accumulates to 90% by volume is set as D90. There is no particular limitation on the value of D90 / D10, and it is preferably 3.2 or less, and more preferably 3 or less. There is no particular limitation on the lower limit, and it is preferably 1 or more. This D90 / D10 of 3.2 or less indicates that the particle size distribution is narrow. If it is such a particle size distribution, it is preferred in that it is easy to control transparency and fluidity when added to a photocurable composition. In addition, by introducing particles with high regularity into the cured film, there is an advantage that the wear resistance and crack resistance of the cured film are improved.

[0071] When using silica particles as inorganic particles, there is no particular restriction on the type of silica particles, and wet-process silica produced by an ion exchange method or a sol-gel method is preferred. In particular, sol-gel silica particles substantially consisting of SiO2 units obtained by hydrolyzing and condensing a tetrafunctional silane compound and / or a (partial) hydrolysis-condensation product thereof are preferred.

[0072] It should be noted that the so-called sol-gel silica particles "basically composed of SiO2 units" means that the particles are basically composed of SiO2 units, but are not composed only of these units, and at least have a large number of silanol groups on the surface as is generally known. In addition, it means that sometimes a part of the hydrolyzable groups (hydrocarbyloxy groups) derived from the tetrafunctional silane compound as a raw material and / or its partial hydrolysis and condensation product may remain on the surface and inside of the particles as they are without being converted into silanol groups.

[0073] As a method for distinguishing silica particles made by the sol-gel method from silica made by the ion exchange method, the Q unit (including Q represented by the following formula) in the siloxane unit is compared. 1 ~Q 4 The proportion of Q 4 The ratio of the units and the comparison of the alkali metal components are effective.

[0074] [Chemistry 3]

[0075]

[0076] (In the formula, X is independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.)

[0077] In the present invention, the Q unit of the siloxane accounts for 4 The proportion of the unit can be 29 The Si-NMR measurement can be obtained, specifically, as the peak area (Q4 ) to the ratio of the peak area (Q) between -80 and -130 ppm (Q 4 / Q) to find out.

[0078] The Q of the silica particles used in the present invention is 4 / Q is usually preferably 0.8 or less, more preferably 0.2 to 0.8, and still more preferably 0.55 to 0.75. (Q 4 When / Q) is 0.2 to 0.8, the abrasion resistance of the cured film becomes more favorable.

[0079] In the present invention, the peak area refers to the area (integral value) when the signal intensity is plotted against the chemical shift value (parts per million (ppm)). The integral is preferably calculated by setting a threshold value according to the S / N ratio of a specific benchmark. For example, the S / N ratio is preferably 5 or more, more preferably 10 or more, and further preferably 20 or more. In the case of less than 5, the baseline sometimes becomes coarse and the accuracy of the integral becomes poor, so it is not preferred. The integral can be calculated by the Simpson method using an electronic calculator, etc., and can also be calculated by cutting a printed medium having a uniform planar density representing the spectrum into a spectrum shape and measuring the mass.

[0080] 29 Si NMR spectroscopy can be performed in both solid and liquid states. However, solid NMR spectroscopy requires drying as a pretreatment for measuring the sample, and is not necessarily limited to the bonding state of silicon reflected in the sample. Therefore, it is preferred to use liquid NMR spectroscopy for confirmation. In this case, 29 Si nuclei have a negative magnetic gyrometry ratio (γ B ), so the nuclear Overhauser effect is opposite, suppressing the nuclear magnetic relaxation existing around the resonant nucleus. Therefore, it is preferable to use measurement conditions in which the negative nuclear Overhauser effect does not become significant.

[0081] In the case of pulsed Fourier transform nuclear magnetic resonance, this problem can be solved by using an appropriate pulse sequence. For example, an off-resonance pulse sequence is preferably used. 29 In Si nuclear magnetic resonance spectroscopy, it is preferred to use silicon-free raw materials for the sample tube and the probe for measurement. Examples of silicon-free raw materials that can be used for nuclear magnetic resonance spectroscopy include polytetrafluoroethylene (Teflon (registered trademark)).

[0082] In liquid 29In the Si nuclear magnetic resonance spectroscopy, in order to shorten the measurement time, an appropriate moderator can be used. As a moderator, a known reagent can be used (for example, Organometallics Magazine, 2008, Vol. 27, No. 4, pp. 500-502 and references therein). In particular, chromium (III) acetylacetonate has excellent solubility in organic solvents and does not cause agglomeration of titanium oxide, so it is excellent. For example, by dissolving chromium (III) acetylacetonate in deuterated chloroform (chloroform-d3) at 1 mol·dm -3 It is preferable to use a solution having a concentration of about 50 Å as a moderator by using a few drops thereof, because both a moderation effect and a deuterium lock effect can be obtained.

[0083] The resonant magnetic field can be expressed in parts per million (ppm) and in tetramethylsilane. 29 The difference in the resonant magnetic field when the resonance of the Si nucleus is used as the reference. According to this notation, the Q unit is mostly in the range of -80 to -130 ppm, the T unit (XSiO 3 / 2 (X is the same as above. Same below.)) is mostly -30 to -80ppm, D unit (X 2 SiO 2 / 2 ) are mostly between -10 and -30ppm, M units (X 3 SiO 1 / 2 ) can be detected in the range of -10 to 15 ppm. The negative value in the table indicates that the resonant magnetic field is different from the baseline on the high magnetic field side. The width of the resonance line depends on the strength of the magnetic field of the nuclear magnetic resonance device used for the measurement. As for the above-mentioned preferred range of the resonance line, as an example, it is the value when a magnetic field of 11.75 T (Tesla) is applied. The magnetic field that can be used for the nuclear magnetic resonance device is preferably greater than 5 T and less than 20 T, more preferably greater than 8 T and less than 15 T, and further preferably greater than 10 T and less than 13 T. When the magnetic field is less than 5 T, sometimes the measurement becomes difficult because the S / N ratio becomes smaller. When the magnetic field exceeds 20 T, sometimes the resonance device becomes large and the measurement becomes difficult.

[0084] (2) Organic silicon compounds

[0085] The organosilicon compound used in the present invention is represented by the following formula (1).

[0086] [Chemistry 4]

[0087]

[0088] In the formula, R 1 is a hydrogen atom or a methyl group, R 2 is an alkylene group having 1 to 20 carbon atoms, R3 are each independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 4 Each independently represents a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, or a halogen atom; and n is an integer of 1 to 3.

[0089] In formula (1), as R 2 The alkylene group has 1 to 20 carbon atoms and may be any of linear, branched or cyclic. Specific examples thereof include methylene, ethylene, trimethylene, propylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, cyclohexylene and the like. When the number of carbon atoms is large (8 or more), the fluidity and storage stability of the surface-modified inorganic particles become particularly good. When the number of carbon atoms is small (3 or less), it is particularly effective in improving the wear resistance when introduced into the cured film.

[0090] As R 3 The alkyl group has 1 to 8 carbon atoms and may be any of linear, branched or cyclic. Specific examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, pentyl, hexyl, cyclopentyl and cyclohexyl. Alkyl groups having 1 to 3 carbon atoms are preferred. Among these, the methyl group having small steric hindrance will not hinder the reaction with the surface of the inorganic particles and is therefore particularly preferred.

[0091] R 4 Each independently represents a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, or a halogen atom. Examples of the halogen atom include fluorine, chlorine, bromine, and iodine atoms.

[0092] As R 4 Examples of the alkoxy group include methoxy, ethoxy, and n-propoxy.

[0093] Among these, an alkoxy group is preferred, and a methoxy group is particularly preferred in consideration of reactivity with the surface of inorganic particles.

[0094] n is an integer of 1 to 3, and in consideration of the reactivity with the surface of the inorganic particles, it is preferably 2 or 3, and more preferably 3. In the formula (1), when n is 2 or 3, R 4 They may be the same group or different groups.

[0095] Specific examples of the organosilicon compound represented by the above formula (1) include:

[0096] (Meth)acryloyloxymethylmethyldimethoxysilane,

[0097] (Meth)acryloyloxymethyltrimethoxysilane,

[0098] (Meth)acryloyloxymethylmethyldiethoxysilane,

[0099] (Meth)acryloyloxymethyltriethoxysilane,

[0100] (Meth)acryloyloxymethyltrihydroxysilane,

[0101] (Meth)acryloyloxymethylethyldimethoxysilane,

[0102] (Meth)acryloyloxymethylpropyldimethoxysilane,

[0103] 2-(Meth)acryloyloxyethylmethyldimethoxysilane,

[0104] 2-(Meth)acryloyloxyethyltrimethoxysilane,

[0105] 2-(Meth)acryloyloxyethylmethyldiethoxysilane,

[0106] 2-(Meth)acryloyloxyethyltriethoxysilane,

[0107] 2-(Meth)acryloyloxyethyltrihydroxysilane,

[0108] 2-(Meth)acryloyloxyethylethyldimethoxysilane,

[0109] 2-(Meth)acryloyloxyethylpropyldimethoxysilane,

[0110] 3-(Meth)acryloxypropylmethyldimethoxysilane,

[0111] 3-(Meth)acryloxypropyltrimethoxysilane,

[0112] 3-(Meth)acryloxypropylmethyldiethoxysilane,

[0113] 3-(Meth)acryloxypropyltriethoxysilane,

[0114] 3-(Meth)acryloxypropyltrihydroxysilane,

[0115] 3-(Meth)acryloxypropylethyldimethoxysilane,

[0116] 3-(Meth)acryloxypropylpropyldimethoxysilane,

[0117] 4-(Meth)acryloyloxybutylmethyldimethoxysilane,

[0118] 4-(Meth)acryloyloxybutyltrimethoxysilane,

[0119] 4-(Meth)acryloyloxybutylmethyldiethoxysilane,

[0120] 4-(Meth)acryloyloxybutyltriethoxysilane,

[0121] 4-(Meth)acryloyloxybutyltrihydroxysilane,

[0122] 4-(Meth)acryloyloxybutylethyldimethoxysilane,

[0123] 4-(Meth)acryloyloxybutylpropyldimethoxysilane,

[0124] 5-(Meth)acryloyloxypentylmethyldimethoxysilane,

[0125] 5-(Meth)acryloyloxypentyltrimethoxysilane,

[0126] 5-(Meth)acryloyloxypentylmethyldiethoxysilane,

[0127] 5-(Meth)acryloyloxypentyltriethoxysilane,

[0128] 5-(Meth)acryloyloxypentyltrihydroxysilane,

[0129] 5-(Meth)acryloyloxypentylethyldimethoxysilane,

[0130] 5-(Meth)acryloyloxypentylpropyldimethoxysilane,

[0131] 6-(Meth)acryloyloxyhexylmethyldimethoxysilane,

[0132] 6-(Meth)acryloyloxyhexyltrimethoxysilane,

[0133] 6-(Meth)acryloyloxyhexylmethyldiethoxysilane,

[0134] 6-(Meth)acryloyloxyhexyltriethoxysilane,

[0135] 6-(Meth)acryloyloxyhexyltrihydroxysilane,

[0136] 6-(Meth)acryloyloxyhexylethyldimethoxysilane,

[0137] 6-(Meth)acryloyloxyhexylpropyldimethoxysilane,

[0138] 7-(Meth)acryloyloxyheptylmethyldimethoxysilane,

[0139] 7-(Meth)acryloyloxyheptyltrimethoxysilane,

[0140] 7-(Meth)acryloyloxyheptylmethyldiethoxysilane,

[0141] 7-(Meth)acryloyloxyheptyltriethoxysilane,

[0142] 7-(Meth)acryloyloxyheptyltrihydroxysilane,

[0143] 7-(Meth)acryloyloxyheptylethyldimethoxysilane,

[0144] 7-(Meth)acryloyloxyheptylpropyldimethoxysilane,

[0145] 8-(Meth)acryloyloxyoctylmethyldimethoxysilane,

[0146] 8-(Meth)acryloyloxyoctyltrimethoxysilane,

[0147] 8-(Meth)acryloyloxyoctylmethyldiethoxysilane,

[0148] 8-(Meth)acryloyloxyoctyltriethoxysilane,

[0149] 8-(Meth)acryloyloxyoctyltrihydroxysilane,

[0150] 8-(Meth)acryloyloxyoctylethyldimethoxysilane,

[0151] 8-(Meth)acryloyloxyoctylpropyldimethoxysilane,

[0152] 9-(Meth)acryloyloxynonylmethyldimethoxysilane,

[0153] 9-(Meth)acryloyloxynonyltrimethoxysilane,

[0154] 9-(Meth)acryloyloxynonylmethyldiethoxysilane,

[0155] 9-(Meth)acryloyloxynonyltriethoxysilane,

[0156] 9-(Meth)acryloyloxynonyltrihydroxysilane,

[0157] 9-(Meth)acryloyloxynonylethyldimethoxysilane,

[0158] 9-(Meth)acryloyloxynonylpropyldimethoxysilane,

[0159] 10-(Meth)acryloyloxydecylmethyldimethoxysilane,

[0160] 10-(Meth)acryloyloxydecyltrimethoxysilane,

[0161] 10-(Meth)acryloyloxydecylmethyldiethoxysilane,

[0162] 10-(Meth)acryloyloxydecyltriethoxysilane,

[0163] 10-(Meth)acryloyloxydecyltrihydroxysilane,

[0164] 10-(Meth)acryloyloxydecylethyldimethoxysilane,

[0165] 10-(Meth)acryloyloxydecylpropyldimethoxysilane,

[0166] 11-(Meth)acryloyloxyundecylmethyldimethoxysilane,

[0167] 11-(Meth)acryloyloxyundecyltrimethoxysilane,

[0168] 11-(Meth)acryloyloxyundecylmethyldiethoxysilane,

[0169] 11-(Meth)acryloyloxyundecyltriethoxysilane,

[0170] 11-(Meth)acryloyloxyundecyltrihydroxysilane,

[0171] 11-(Meth)acryloyloxyundecylethyldimethoxysilane,

[0172] 11-(Meth)acryloyloxyundecylpropyldimethoxysilane,

[0173] 12-(Meth)acryloyloxydodecylmethyldimethoxysilane,

[0174] 12-(Meth)acryloyloxydodecyltrimethoxysilane,

[0175] 12-(Meth)acryloyloxydodecylmethyldiethoxysilane,

[0176] 12-(Meth)acryloyloxydodecyltriethoxysilane,

[0177] 12-(Meth)acryloyloxydodecyltrihydroxysilane,

[0178] 12-(Meth)acryloyloxydodecylethyldimethoxysilane,

[0179] 12-(Meth)acryloyloxydodecylpropyldimethoxysilane,

[0180] 13-(Meth)acryloyloxytridecylmethyldimethoxysilane,

[0181] 13-(Meth)acryloyloxytridecyltrimethoxysilane,

[0182] 13-(Meth)acryloyloxytridecylmethyldiethoxysilane,

[0183] 13-(Meth)acryloyloxytridecyltriethoxysilane,

[0184] 13-(Meth)acryloyloxytridecyltrihydroxysilane,

[0185] 13-(Meth)acryloyloxytridecylethyldimethoxysilane,

[0186] 13-(Meth)acryloyloxytridecylpropyldimethoxysilane,

[0187] 14-(Meth)acryloyloxytetradecylmethyldimethoxysilane,

[0188] 14-(Meth)acryloyloxytetradecyltrimethoxysilane,

[0189] 14-(Meth)acryloyloxytetradecylmethyldiethoxysilane,

[0190] 14-(Meth)acryloyloxytetradecyltriethoxysilane,

[0191] 14-(Meth)acryloyloxytetradecyltrihydroxysilane,

[0192] 14-(Meth)acryloyloxytetradecylethyldimethoxysilane,

[0193] 14-(meth)acryloyloxytetradecylpropyldimethoxysilane, etc. These may be used alone or in combination of two or more.

[0194] Among these, compounds represented by the following formulae (2) to (4) are particularly preferred.

[0195] [Chemistry 5]

[0196]

[0197] (Where R 1 , R 3 , R 4 and n are the same as above. )

[0198] In particular, 3-(meth)acryloxypropyltrimethoxysilane, 8-(meth)acryloxyoctyltrimethoxysilane, and (meth)acryloxymethyltrimethoxysilane are preferred from the viewpoint of improving the abrasion resistance of the coating film and easiness of obtaining.

[0199] The amount of the organosilicon compound represented by the above formula (1) used is 1 to 30 parts by mass, preferably 10 to 20 parts by mass, relative to 100 parts by mass of the inorganic particles, from the viewpoint of improving abrasion resistance due to increased crosslinking density and improving dispersibility and fluidity in the photocurable composition.

[0200] (3) Other silane compounds

[0201] The surface-modified inorganic particles of the component (A) may be further surface-modified using one or more silane compounds represented by the following formula (5) and / or the following formula (6).

[0202] R 5 3SiY(5)

[0203] R 5 3Si-NH-SiR 5 3(6)

[0204] In the above formula (5), R 5 Each independently is a monovalent hydrocarbon group having 1 to 20 carbon atoms, preferably a monovalent hydrocarbon group having 1 to 4 carbon atoms, more preferably a monovalent hydrocarbon group having 1 to 2 carbon atoms.

[0205] By R 5 The monovalent hydrocarbon group represented by may be any of linear, branched, and cyclic, and examples thereof include alkyl, alkenyl, aryl, and aralkyl groups.

[0206] As R 5 Specific examples of the monovalent hydrocarbon group include, for example, alkyl groups such as methyl, ethyl, n-propyl, isopropyl, and n-butyl; alkenyl groups such as vinyl and allyl; aryl groups such as phenyl and tolyl; aralkyl groups such as 2-phenylethyl and 2-phenylpropyl. Among these, alkyl groups such as methyl, ethyl, and n-propyl are preferred, and methyl and ethyl are particularly preferred. In addition, part or all of the hydrogen atoms of these monovalent hydrocarbon groups may be substituted with halogen atoms such as fluorine, chlorine, and bromine, preferably fluorine atoms.

[0207] Y is a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, an amino group, an acyloxy group, or a halogen atom. Examples of the alkoxy group include a methoxy group, an ethoxy group, and an n-propoxy group, examples of the amino group include an N,N-dimethylamino group, an N,N-diethylamino group, examples of the acyloxy group include an acetoxy group, and examples of the halogen atom include the same halogen atoms as described above. Among these, a hydroxyl group and a methoxy group are preferred.

[0208] Specific examples of the compound represented by formula (5) include monosilanol compounds such as trimethylsilanol and triethylsilanol; monochlorosilanes such as trimethylchlorosilane and triethylchlorosilane; monoalkoxysilanes such as trimethylmethoxysilane and trimethylethoxysilane; monoaminosilanes such as trimethylsilyldimethylamine and trimethylsilyldiethylamine; monoacyloxysilanes such as trimethylacetoxysilane, etc. These may be used alone or in combination of two or more.

[0209] Among these, trimethylsilanol, trimethylmethoxysilane, and trimethylsilyldiethylamine are preferred, and trimethylsilanol and trimethylmethoxysilane are particularly preferred.

[0210] Specific examples of the compound represented by formula (6) include hexamethyldisilazane, hexaethyldisilazane, hexapropyldisilazane, hexa(n-butyl)disilazane, hexa(isobutyl)disilazane, hexa(tert-butyl)disilazane, hexapentyldisilazane, hexahexyldisilazane, hexaheptyldisilazane, hexaoctyldisilazane, hexa(2-ethylhexyl)disilazane, etc. These may be used alone or in combination of two or more.

[0211] Among these, hexamethyldisilazane is preferred.

[0212] When using the compound represented by the above formula (5) and / or the above formula (6), the amount used is preferably 1 to 20 parts by mass, more preferably 5 to 15 parts by mass, and particularly preferably 8 to 12 parts by mass relative to 100 parts by mass of the inorganic particles. When the amount used is 20 parts by mass or less, the remaining unreacted silane compound can be suppressed, and the wear resistance of the cured product becomes good, so it is preferred. When it is 1 part by mass or more, the storage stability of the inorganic particle dispersion becomes good, so it is preferred.

[0213] The median diameter (D50) of the particle size distribution of the surface-modified inorganic particles of component (A) at which 50% of the cumulative volume is obtained is 1 to 60 nm, preferably 5 to 40 nm, and more preferably 10 to 30 nm. When D50 is less than 1 nm, the wear resistance of the cured film is poor, and when D50 exceeds 60 nm, the transparency of the cured film is impaired.

[0214] The median diameter can be measured by a dynamic light scattering method using laser light, using an apparatus such as NANOTRAC UPA-EX150 (manufactured by Nikkiso Co., Ltd.), for example.

[0215] In the volume-based particle size distribution of the surface-modified inorganic particles by dynamic light scattering, the value of D90 / D10 is not particularly limited, but is preferably 3.2 or less, and more preferably 3 or less. The lower limit is not particularly limited, but is preferably 1 or more.

[0216] The amount of component (A) in the photocurable composition is 10 to 35% by mass, preferably 20 to 30% by mass. When the content of the surface-modified inorganic particles is less than 10% by mass, the photocurability and abrasion resistance are insufficient, and when it exceeds 35% by mass, the viscosity of the composition increases excessively.

[0217] The component (A) may be added to the photocurable composition of the present invention in a powder state, but it is preferably prepared in advance as a dispersion using the difunctional (meth)acrylate of the component (B) and / or the trifunctional (meth)acrylate of the component (C) as a dispersion medium and then mixed into the composition, thereby suppressing the amount of the volatile organic solvent used and preventing the aggregation of particles.

[0218] (4) Method for producing surface-modified inorganic particles

[0219] Next, an example of the method for producing the surface-modified inorganic particles of the present invention will be described in detail.

[0220] The component (A) used in the present invention is surface-modified inorganic particles obtained by surface-treating inorganic particles. When silica particles are used as inorganic particles, for example, they can be produced by a method including the following steps (α), (β), and if necessary (γ).

[0221] Step (α): Synthesis step of sol-gel silica particles,

[0222] Step (β): a sol-gel silica surface treatment step using an organic silicon compound,

[0223] Step (γ): dispersion medium replacement step.

[0224] Each step is described below.

[0225] Step (α): Synthesis step of sol-gel silica particles

[0226] Step (α) is a step of obtaining an organic solvent / water dispersion of hydrophilic sol-gel silica particles by hydrolyzing and condensing at least one of a silane compound represented by the following formula (7), a (partial) hydrolyzate and a condensate thereof in the presence of an alkaline substance in a mixed solvent of a hydrophilic organic solvent and water.

[0227] Si(OR 6 )4(7)

[0228] In the above formula (7), R 6 Each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms.

[0229] As R 6 The monovalent hydrocarbon group may be 5 The groups having 1 to 6 carbon atoms among the groups exemplified in are preferably groups having 1 to 4 carbon atoms, more preferably alkyl groups such as methyl, ethyl, n-propyl, and n-butyl, and particularly preferably methyl and ethyl.

[0230] Specific examples of the silane compound represented by the formula (7) include tetraalkoxysilanes such as tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, and tetra-n-butoxysilane; and tetraaryloxysilanes such as tetraphenoxysilane.

[0231] Among these, tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, and tetra-n-butoxysilane are preferred, and tetramethoxysilane and tetraethoxysilane are particularly preferred. In addition, examples of their hydrolysis condensates include methyl silicate and ethyl silicate.

[0232] The hydrophilic organic solvent used for hydrolyzing and condensing the above-mentioned silane compound is not particularly limited as long as it is an organic solvent that dissolves the silane compound represented by the above-mentioned formula (7), at least one of its (partial) hydrolyzate and condensate, and water. Examples thereof include alcohols such as methanol, ethanol, n-propanol, isopropanol, and n-butanol; cellosolves such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, and acetic cellosolve; ketones such as acetone and methyl ethyl ketone; ethers such as dioxane and tetrahydrofuran, and the like.

[0233] Among these, alcohols and cellosolves are preferred, alcohols are more preferred, and methanol and ethanol are particularly preferred. If the number of carbon atoms in the alcohol increases, the particle size of the generated spherical silica particles becomes larger. Therefore, in order to obtain the target small-particle-size silica particles, methanol is preferred.

[0234] In addition, specific examples of the alkaline substance include ammonia, dimethylamine, diethylamine, etc., preferably ammonia and diethylamine, and particularly preferably ammonia. The required amount of these alkaline substances can be dissolved in water and the resulting aqueous solution (alkaline) can be mixed with the hydrophilic organic solvent.

[0235] The amount of water used in step (α) is preferably 0.5 to 5 mol, more preferably 0.6 to 3 mol, particularly preferably 0.7 to 2 mol, based on 1 mol of the total hydrocarbyloxy groups of the silane compound represented by the above formula (7), its (partial) hydrolyzate and condensate.

[0236] The ratio of the hydrophilic organic solvent to water, expressed as a mass ratio, is preferably 0.5 to 10, more preferably 2 to 9, and particularly preferably 3 to 8. In this case, the larger the amount of the hydrophilic organic solvent, the smaller the particle size of the silica particles.

[0237] The amount of the alkaline substance is preferably 0.01 to 2 mol, more preferably 0.02 to 0.5 mol, and particularly preferably 0.04 to 0.12 mol, relative to 1 mol of the total hydrocarbyloxy group of at least one of the tetrafunctional silane compound represented by the general formula (7), its (partial) hydrolyzate, and condensate. In this case, the smaller the amount of the alkaline substance, the smaller the particle size of the silica particles.

[0238] The hydrolysis and condensation of the silane compound represented by the above formula (7) can be carried out by a known method, for example, by adding the above silane compound to a mixture of a hydrophilic organic solvent containing a basic substance and water.

[0239] After the silane compound represented by the above formula (7) is added, the reaction is preferably carried out at a reaction temperature of 20 to 120° C. for a reaction time of 1 to 8 hours, and more preferably at a reaction temperature of 20 to 100° C. for a reaction time of 1 to 6 hours.

[0240] The concentration of the sol-gel silica particles in the organic solvent / water dispersion in step (α) is preferably 5 to 30% by mass, more preferably 10 to 25% by mass.

[0241] ·Step (β): Silica surface treatment step

[0242] This step is a step of adding at least one of an organosilicon compound represented by the following formula (1), a (partial) hydrolyzate thereof and a condensate thereof to the dispersion of the hydrophilic sol-gel silica particles obtained in step (α) to treat the surface of the hydrophilic spherical silica particles.

[0243] [Chemistry 6]

[0244]

[0245] (Where R 1 , R 2 , R 3 , R 4 and n are the same as above. )

[0246] Examples of the organosilicon compound represented by the formula (1) include the same organosilicon compounds as those exemplified above, and the amount used is also the same as above.

[0247] The silica particles used in the present invention may be surface-modified using one or more silane compounds represented by the following formula (5) and / or the following formula (6).

[0248] R 5 3SiY(5)

[0249] R 5 3Si-NH-SiR 5 3(6)

[0250] (Where R 5 and Y are the same as above. )

[0251] Examples of the compounds represented by the formulae (5) and (6) include the same compounds as those exemplified above, and the amounts used are also the same as those described above.

[0252] In addition, in order to promote the reaction between the above-mentioned organosilicon compound and the silane compound sometimes used and the silica surface, the hydrophilic spherical silica particle dispersion used in the step (β) preferably contains an alkaline substance. As the alkaline substance, the same alkaline substance as the alkaline substance exemplified in the step (α) can be listed, preferably ammonia, diethylamine, and particularly preferably ammonia. In the case of using ammonia, since the surface treatment efficiency is improved, it can also be removed by distillation, so it is effective for simplifying the refining process.

[0253] When a basic substance is used, the amount thereof is preferably 1 to 5 mol, more preferably 2 to 3 mol, per 1 mol of the hydrolyzable group of the compound represented by the above formula (1) or (5) and / or (6) which is used in some cases.

[0254] The conditions for the hydrolysis condensation reaction (surface treatment) in step (β) can be carried out under the same conditions as step (α). For example, it is preferably carried out at a reaction temperature of 20 to 120° C. and a reaction time of 1 to 8 hours, and more preferably at a reaction temperature of 20 to 100° C. and a reaction time of 1 to 6 hours.

[0255] ·Step (γ): Dispersion medium replacement step

[0256] This step is a step of adding the difunctional (meth)acrylate of the component (B) and / or the trifunctional (meth)acrylate of the component (C) described later to the dispersion of silica particles surface-treated with an organosilicon compound obtained in step (β) as necessary, and removing the hydrophilic organic solvent, water, and alcohol that may be generated by condensation by distillation.

[0257] In this case, (B) difunctional (meth)acrylate and / or (C) trifunctional (meth)acrylate may be added to the dispersion in advance or added to the dispersion after the alcohol etc. are distilled off. Preferably, they are added to the dispersion in advance and then distilled off.

[0258] According to this step, a silica dispersion in which silica particles surface-treated with an organic silicon compound are dispersed in (B) a difunctional (meth)acrylate and / or (C) a trifunctional (meth)acrylate is obtained.

[0259] Examples of a method for distilling off the hydrophilic organic solvent, water, and volatile by-products such as alcohol generated by condensation include distillation under atmospheric pressure and distillation under reduced pressure, and distillation under reduced pressure is preferred.

[0260] When heating is performed under reduced pressure distillation, the temperature is preferably 30 to 100° C., more preferably 40 to 80° C., and even more preferably 50 to 70° C. Heating to 30° C. or higher is preferred because the time required for solvent distillation can be shortened, and thus, heating to 100° C. or lower is preferred because side reactions such as polymerization of acrylic compounds and transesterification of solvents with acrylic acid moieties caused by heat can be suppressed, and the scratch resistance of the cured film obtained when the composition is added to a photocurable composition may sometimes be improved, and thus, this is preferred.

[0261] The amount of difunctional (meth)acrylate and / or trifunctional (meth)acrylate added is not particularly limited. In the silica dispersion obtained by step (γ), the surface-treated silica particles are preferably dispersed in 5 to 250 parts by mass, more preferably 10 to 200 parts by mass, further preferably 25 to 150 parts by mass, and most preferably 50 to 125 parts by mass, relative to 100 parts by mass of (B) difunctional (meth)acrylate and / or (C) trifunctional (meth)acrylate. When silica is dispersed in 5 parts by mass or more and added to the photocurable composition, the abrasion resistance of the obtained cured film is improved. When it is dispersed in 250 parts by mass or less, the fluidity of the dispersion is improved.

[0262] The silica dispersion thus obtained may contain additives such as an alkali neutralizer, an acid neutralizer, an alkali adsorbent, an acid adsorbent, a polymerization inhibitor, an antioxidant, an ultraviolet absorber, and a light stabilizer, so long as the effects of the present invention are not impaired, to improve storage stability.

[0263] <(B) Bifunctional (meth)acrylate>

[0264] (B) component is a difunctional (meth)acrylate. Examples of the difunctional (meth)acrylate of component (B) include dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate (HDDA), tetraethylene glycol diacrylate, neopentyl glycol diacrylate, 3-methyl-1,5-pentanediol diacrylate, 1,9-nonanediol diacrylate, dihydroxymethyl-tricyclodecane diacrylate, hydroxypivalic acid neopentyl glycol acrylate adduct, 2-hydroxy-3-acryloyloxypropyl methacrylate, ethylene glycol diacrylate, polyethylene glycol (n=2-15) diacrylate, polypropylene glycol (n=2-15) diacrylate, polybutylene glycol (n=2-15) diacrylate, trimethylolpropane diacrylate, and the like. These compounds may be used alone or in combination of two or more.

[0265] Among these, dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate (HDDA), tetraethylene glycol diacrylate, neopentyl glycol diacrylate, 3-methyl-1,5-pentanediol diacrylate, and 1,9-nonanediol diacrylate are particularly preferred from the viewpoint of curability and low viscosity.

[0266] The amount of the difunctional (meth)acrylate of component (B) is preferably 10% by mass or more, more preferably 10 to 45% by mass, and further preferably 20 to 45% by mass relative to the entire photocurable composition. When the content of the difunctional (meth)acrylate compound is 10% by mass or more, thickening of the composition can be prevented, and therefore, it is preferred that the content of the difunctional (meth)acrylate compound is 45% by mass or less, because photocurability and scratch resistance become good, and therefore, it is preferred.

[0267] <(C) Trifunctional (meth)acrylate>

[0268] (C) component is a trifunctional (meth)acrylate. As the trifunctional (meth)acrylate of (C) component, for example, trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxy triacrylate, glycerol propoxy triacrylate, tris (2-acryloyloxyethyl) isocyanurate, pentaerythritol triacrylate, etc. can be listed. These can be used alone or in combination of two or more.

[0269] Among these, trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxy triacrylate, and glycerol propoxy triacrylate are particularly preferred from the viewpoint of curability and low viscosity.

[0270] The amount of component (C) is preferably 5% by mass or more, more preferably 5 to 75% by mass, and further preferably 9 to 70% by mass relative to the entire photocurable composition. When the content of the trifunctional (meth)acrylate compound is 5% by mass or more, photocurability and abrasion resistance become good, so it is preferred, and when the content of the trifunctional (meth)acrylate compound is 75% by mass or less, it is possible to prevent the thickening of the composition, so it is preferred.

[0271] The total amount of the components (A), (B) and (C) is 70% by mass or more, preferably 70 to 98% by mass, and more preferably 80 to 95% by mass, relative to the total composition. When the amount is less than 70% by mass, the photocurability and abrasion resistance are insufficient.

[0272] <(D) Photoradical initiator>

[0273] (D) component is a photoradical initiator. Specific examples of the photoradical initiator of component (D) include acetophenone, propiophenone, 2,2-dimethoxy-1,2-diphenylethane-1-one (OMNIRAD 651: manufactured by IGM RESINS), 2-hydroxy-2-methyl-1-phenyl-propane-1-one (OMNIRAD 1173: manufactured by IGM RESINS), 1-hydroxy-cyclohexyl-phenyl-ketone (OMNIRAD 184: manufactured by IGM RESINS), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one (OMNIRAD 2959: manufactured by IGM RESINS), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one (OMNIRAD 127: manufactured by IGM RESINS). RESINS), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (OMNIRAD 907: manufactured by IGM RESINS), 2-benzyl-2-dimethylamino-(4-morpholinophenyl)-butanone-1 (OMNIRAD 369: manufactured by IGM RESINS), 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone (OMNIRAD 379: manufactured by IGM RESINS); 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (OMNIRAD TPO-H: manufactured by IGM RESINS), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (OMNIRAD 819: manufactured by IGM RESINS). RESINS); 1,2-octanedione, 1-[4-(phenylthio)-, 2-(o-benzoyl oxime)] (IRGACURE OXE 01: BASF), ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(o-acetyl oxime) (IRGACURE OXE 02: BASF); a mixture of oxyphenylacetic acid, 2-[2-oxo-2-phenylacetoxyethoxy]ethyl ester and oxyphenylacetic acid, 2-(2-hydroxyethoxy)ethyl ester (OMNIRAD 754: IGM RESINS), methyl phenylglyoxylate (OMNIRAD MBF: IGM RESINS), ethyl-4-dimethylaminobenzoate (DAROCUR EDB: IGM RESINS Co., Ltd.), 2-ethylhexyl-4-dimethylaminobenzoate, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, benzoyl peroxide, cumene peroxide, and the like.These may be used alone or in combination of two or more.

[0274] The component (D) preferably contains both an alkylphenone compound and an acylphosphine oxide compound from the viewpoint of improving photocurability and abrasion resistance, and more preferably contains in combination a compound selected from 2-hydroxy-2-methyl-1-phenyl-propane-1-one (OMNIRAD 1173: manufactured by IGM RESINS), 1-hydroxy-cyclohexyl-phenyl-ketone (OMNIRAD 184: manufactured by IGM RESINS), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one (OMNIRAD 2959: manufactured by IGM RESINS), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one (OMNIRAD 127: manufactured by IGM RESINS), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one (OMNIRAD 306: manufactured by IGM RESINS), and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one (OMNIRAD 306: manufactured by IGM RESINS). Alkyl phenone compounds selected from OMNIRAD 907: manufactured by IGM RESINS), 2-benzyl-2-dimethylamino-(4-morpholinophenyl)-butanone-1 (OMNIRAD 369: manufactured by IGM RESINS), 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone (OMNIRAD 379: manufactured by IGM RESINS), and acyl phosphine oxide compounds selected from 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (OMNIRAD TPO-H: manufactured by IGM RESINS), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (OMNIRAD 819: manufactured by IGM RESINS), etc.

[0275] The amount of component (D) is preferably 2 to 15% by mass, more preferably 5 to 10% by mass, relative to the total amount of the photocurable composition. When the content of the photoradical initiator is 2% by mass or more, the photocurability and abrasion resistance become good, so it is preferred, and when the content of the photoradical initiator is 15% by mass or less, it is preferred because yellowing and a decrease in abrasion resistance can be prevented.

[0276] <(E) Other (meth)acrylates>

[0277] The photocurable composition of the present invention may contain a monofunctional (meth)acrylate or a tetrafunctional or higher polyfunctional (meth)acrylate in addition to the above-mentioned (B) difunctional (meth)acrylate and (C) trifunctional (meth)acrylate, within a range not inhibiting the effects of the present invention.

[0278] Examples of the monofunctional (meth)acrylate include ethyl acrylate, butyl acrylate, ethylhexyl acrylate, 2-hydroxyethyl acrylate, isobornyl acrylate, and tetrahydrofurfuryl acrylate.

[0279] Examples of the polyfunctional (meth)acrylate include pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate (DPHA), caprolactone-modified dipentaerythritol hexaacrylate (acrylate of an adduct of dipentaerythritol and ε-caprolactone), caprolactone-modified dipentaerythritol hydroxypentaacrylate, di(trimethylolpropane) tetraacrylate, N-vinyl pyrrolidone, aliphatic urethane acrylate oligomers, aliphatic polyester acrylate oligomers, and the like.

[0280] Among these, ethoxylated pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate (DPHA) are preferred.

[0281] When a tetrafunctional or higher polyfunctional (meth)acrylate is added, it is preferred that the amount thereof is less than 20% by mass based on the total mass of the photocurable composition because this prevents the composition from thickening and improves photocurability and abrasion resistance.

[0282] <(F) Ultraviolet light absorber>

[0283] The photocurable composition of the present invention may contain an ultraviolet absorber within the range that does not impair the effect of the present invention. As the ultraviolet absorber, there can be listed ultraviolet absorbers of benzotriazole series, triazine series, benzophenone series, benzoate series, etc., and as specific examples, there can be listed 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole (RUVA-93; manufactured by Otsuka Chemical Co., Ltd.), 2,4-dihydroxybenzophenone (manufactured by Tokyo Chemical Industry Co., Ltd.), 2,3,4-trihydroxybenzophenone (manufactured by Tokyo Chemical Industry Co., Ltd.), 2,2',4,4'-tetrahydroxybenzophenone (manufactured by Tokyo Chemical Industry Co., Ltd.), 2,2'-dimethoxy-4,4'-dimethoxybenzophenone (manufactured by Tokyo Chemical Industry Co., Ltd.), Tinuvin 405 (manufactured by BASF Corporation; 2- [4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine), Tinuvin 400 (manufactured by BASF; 2-[4-{(hydroxy-3-dodecyloxypropyl)oxy}-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine), Tinuvin 479 (manufactured by BASF; 2-[2-hydroxy-4-(1-octyloxycarbonylethoxy)phenyl]-4,6-bis(4-phenylphenyl)-1,3,5-triazine), ultraviolet absorbers described in Japanese Patent No. 6156214 and Japanese Patent No. 6354665, etc. The above ultraviolet absorbers may be used alone or in combination of two or more.

[0284] Among these, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, 2-[2-hydroxy-4-(1-octyloxycarbonylethoxy)phenyl]-4,6-bis(4-phenylphenyl)-1,3,5-triazine, and ultraviolet absorbers described in Japanese Patent No. 6354665 are preferred.

[0285] The amount of the ultraviolet absorber used is preferably 1 to 15% by mass, more preferably 5 to 10% by mass, relative to the photocurable composition. When the content of the ultraviolet absorber is 1% by mass or more, weather resistance is improved, so it is preferred, and when it is 15% by mass or less, yellowing, poor curing, and a decrease in wear resistance can be prevented, so it is preferred.

[0286] <Other additives>

[0287] The photocurable composition of the present invention may contain additives such as a polymerization inhibitor, an antioxidant, a light stabilizer, and a leveling agent within a range not impairing the effects of the present invention.

[0288] Examples of the polymerization inhibitor include hydroquinone, p-methoxyphenol, tert-butylcatechol, phenothiazine, benzofuroxan, nitrosobenzene, 2-methyl-2-nitrosopropane dimer, and N-tert-butyl-α-phenylnitrone.

[0289] When a polymerization inhibitor is used, the amount thereof is about 100 to 10000 ppm based on the mass of the organosilicon compound having a (meth)acryloyl group used in the composition.

[0290] Examples of the antioxidant include hindered amine-based antioxidants and hindered phenol-based antioxidants.

[0291] Examples of hindered amine antioxidants include N,N',N",N"'-tetrakis-(4,6-bis(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazine-2-yl)-4,7-diazadecane-1,10-diamine, dibutylamine / 1,3,5-triazine / N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl-1,6-hexamethylenediamine / N-(2,2,6,6-tetramethyl-4-piperidinyl)butyl condensation products of 1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}], polymers of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol, [bis(2,2,6,6-tetramethyl-1(octyloxy)-4-piperidinyl) sebacate, Reaction product of 1,1-dimethylethyl hydroperoxide and octane (70% by mass)]-polypropylene (30% by mass), bis(1,2,2,6,6-pentamethyl-4-piperidinyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate, methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4

[0063] The present invention also includes, but is not limited to, 1-[2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl]-4-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]-2,2,6,6-tetramethylpiperidine, 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, 8-acetyl-3-dodecyl-7,7,9,9-tetramethyl-1,3,8-triazaspiro[4.5]decane-2,4-dione, and the like.

[0292] Examples of the hindered phenol antioxidant include pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)], phenylpropionic acid 3,5-bis(1,1-dimethylethyl)-4-hydroxy C7-C9 side chain alkyl ester, 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 3,3',3",5,5',5"-hexane-tert-butyl-4-a,a',a" -(mesitylene-2,4,6-tolyl) tri-p-cresol, diethyl bis[[[3,5-bis-(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate calcium], 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxy The present invention also includes, but is not limited to, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, a reaction product of N-phenylaniline and 2,4,4-trimethylpentene, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, and the like.

[0293] The above antioxidants may be used alone or in combination of two or more.

[0294] Examples of the light stabilizer include benzotriazole-based, hindered amine-based, and benzoate-based compounds.

[0295] As a light stabilizer, a hindered amine system is preferred. Among them, a hindered amine light stabilizer containing a tertiary amine is preferred because the storage stability of the composition is improved. As a hindered amine light stabilizer containing a tertiary amine, TINUVIN622LD, TINUVIN 144, TINUVIN 123, CHIMASSORB119FL (all manufactured by BASF); MARKLA-57, LA-62, LA-67, LA-63 (all manufactured by Asahi Denka Co., Ltd.); SANOL LS-765, LS-292, LS-2626, LS-1114, LS-744 (all manufactured by Sankyo Co., Ltd.) and other light stabilizers can be listed.

[0296] Examples of the leveling agent include "KP-341" manufactured by Shin-Etsu Chemical Co., Ltd., "BYK-180" and "BYK-190" manufactured by BYK Chemie, and "LE-604" manufactured by Kyoeisha Chemical Co., Ltd.

[0297] In addition, in addition to the above-mentioned additives, silicone resins, pigments, dyes, metal powders, heat ray reflection / absorption imparting agents, flexibility imparting agents, antistatic agents, antifouling imparting agents, water repellency imparting agents, etc. can be added to the photocurable composition of the present invention as needed.

[0298] In the photocurable composition of the present invention, from the perspective of reducing the load on the environment, the content of the volatile organic solvent relative to the entire composition is preferably less than 10% by mass, more preferably less than 5% by mass, and particularly preferably less than 1% by mass. It should be noted that the solvent also includes components not intentionally added to the composition, such as a reaction solvent that cannot be completely removed by vacuum distillation and an alcohol generated by hydrolysis of an alkoxysilyl group.

[0299] The kinematic viscosity of the photocurable composition of the present invention at 25° C. is preferably 100 mm 2 / s or less, preferably 75mm 2 / s or less, more preferably 50mm 2 / s or less. The kinematic viscosity at 25°C is 100 mm 2 When the viscosity is less than 200 μm, the coating workability is improved and a coating method suitable for coating low-viscosity liquids such as flow coating and spray coating can be used, which is preferred. 2 / s) can be measured using a Cannon-Fenske viscometer (manufactured by Shibata Corporation) or the like.

[0300] [cured material]

[0301] The photocurable composition of the present invention can be cured by irradiating ultraviolet rays under an atmosphere such as air or nitrogen. Examples of lamps in the wavelength region of the reactive range include high pressure mercury lamps (UV-7000) manufactured by Ushio Electric Co., Ltd., metal halide lamps (MHL-250, MHL-450, MHL-150, MHL-70), metal halide lamps (JM-MTL2KW) manufactured by JMtech, ultraviolet irradiation lamps (OSBL360) manufactured by Mitsubishi Electric Co., Ltd., ultraviolet irradiation machine (UD-20-2) manufactured by Nippon Battery Co., Ltd., fluorescent lamps (FL-20BLB) manufactured by Toshiba Co., Ltd., H bulbs, HPlus bulbs, D bulbs, Q bulbs, M bulbs, etc. manufactured by Fusion Co., Ltd.

[0302] The irradiation dose is preferably 100 to 12000 mJ / cm 2 , more preferably 300 to 8000 mJ / cm 2 , more preferably 500 to 6000 mJ / cm 2 .

[0303] When the composition of the present invention is cured by irradiating it with ultraviolet rays in an air atmosphere, a tendency is particularly observed to improve the abrasion resistance. Therefore, it is preferred to irradiate the composition of the present invention with ultraviolet rays in an air atmosphere.

[0304] [covered items]

[0305] By applying the photocurable composition of the present invention directly or through at least one other layer onto at least one surface of a substrate and curing it by irradiation with light as described above, a coated article having a film formed thereon can be obtained.

[0306] The substrate is not particularly limited, and examples thereof include plastic molded products, wood products, ceramics, glass, metals, and composites thereof.

[0307] Furthermore, it is also possible to use substrates whose surfaces have been treated, specifically, substrates treated with chemical conversion treatment, corona discharge treatment, plasma treatment, acid, alkali solution, etc., and cosmetic plywood in which the substrate body and the surface layer are coated with different types of coatings, etc. In particular, when a cured film composed of the photocurable composition of the present invention is formed on a polycarbonate substrate, the wear resistance and weather resistance of the polycarbonate can be improved.

[0308] Furthermore, the surface of a substrate on which another functional layer has been formed in advance may be coated with the photocurable composition of the present invention.

[0309] Examples of other functional layers include a primer layer, a rust-proof layer, a gas barrier layer, a water-repellent layer, and a heat-ray shielding layer. Any one or more of these layers may be formed in advance on the substrate.

[0310] It should be noted that, in the case of the coated article, the surface on which the cured film composed of the above composition is formed may be further coated with one or more layers of a vapor-deposited layer obtained by chemical vapor deposition (CVD), a hard coating layer, a rust-proof layer, a gas barrier layer, a waterproof layer, a heat ray shielding layer, an antifouling layer, a photocatalyst layer, an antistatic layer, etc. Furthermore, in the case of the coated article, the surface opposite to the surface on which the cured film composed of the above composition is formed may be coated with one or more layers of a hard coating layer, a rust-proof layer, a gas barrier layer, a waterproof layer, a heat ray shielding layer, an antifouling layer, a photocatalyst layer, an antistatic layer, etc.

[0311] The method for applying the photocurable composition of the present invention may be appropriately selected from known methods, and various coating methods such as brush coating, spraying, dipping, flow coating, roll coating, curtain coating, spin coating, and knife coating may be used.

[0312] The thickness of the cured film in the coated article of the present invention is not particularly limited and can be appropriately selected according to the intended use, preferably 0.1 to 50 μm, and particularly preferably 1 to 20 μm in order to satisfy the hardness, abrasion resistance, long-term stable adhesion and no cracking of the cured film. The film thickness can be appropriately adjusted by the coating amount, etc.

[0313] One of the characteristics of the coated article of the present invention is the visible light transmittance of the cured film. Visible light transmittance is generally evaluated by the haze (Haze), %) of the cured film. The smaller the haze, the better the visible light transmittance. The haze can be measured using a turbidity meter NDH2000 (manufactured by Nippon Denshoku Industries). As for the haze of the cured film, generally the greater the film thickness, the greater the haze. As for the coated article of the present invention, when the film thickness of the cured film is less than 5 μm, the haze is preferably less than 2.0, more preferably less than 1.5, and further preferably less than 1.0.

[0314] One of the characteristics of the coated article of the present invention is the excellent wear resistance of the cured film. As for the wear resistance, according to ASTM1044, the wear wheel SC-10F is installed in the Taper wear test, and the haze difference (ΔHz, % point) before and after the test is compared when the haze after 500 turns under a load of 500 gf is measured. The smaller the ΔHz, the better the wear resistance can be judged. For the coated article of the present invention, ΔHz is preferably 10 or less, more preferably 8 or less, and further preferably 6 or less.

[0315] Example

[0316] The present invention will be described in detail below by showing synthesis examples, examples and comparative examples. It should be noted that the following examples do not limit the present invention in any way.

[0317] [1] Preparation of surface modified silica dispersion

[0318] [Synthesis example 1]

[0319] Process (α):

[0320] In a 1-liter glass reactor equipped with a stirrer, a dropping funnel, and a thermometer, 396 g of methanol, 16 g of water, and 20 g of 28% by mass ammonia water were added and mixed. The solution was adjusted to 50°C, and 323 g of tetramethoxysilane and 81 g of 5.5% by mass ammonia water were simultaneously added dropwise while stirring. After the addition was completed, stirring was continued at 50°C for 1 hour to hydrolyze and obtain a sol-gel silica particle dispersion. The non-volatile content of the obtained dispersion (105°C, 3 hours) was 18% by mass.

[0321] Process (β):

[0322] 22.6 g of 3-methacryloxypropyltrimethoxysilane was added to 837 g of the sol-gel silica particle dispersion obtained in the above step (α) at ​​25° C., and stirring was continued for 2 hours. Then, 15.1 g of trimethylsilanol (LS-310: manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and stirring was continued for 1 hour to obtain a water-methanol dispersion of surface-modified silica particles (A-1).

[0323] Process (γ):

[0324] To the water-methanol dispersion of the surface-modified silica particles (A-1) obtained in the above step (β), 1,6-hexanediol diacrylate (HDDA: manufactured by Daicel, component B-1) in an amount equivalent to the mass of the silica particles was added at 25° C., and then the low-boiling point components in the dispersion were distilled off at 50° C. under reduced pressure (6650 Pa) to obtain a 50% by mass HDDA (B-1) dispersion of the surface-modified silica particles (A-1).

[0325] [Synthesis example 2]

[0326] A 50 mass % HDDA (B-1) dispersion of surface-modified silica particles (A-2) was obtained by the same procedure as in Synthesis Example 1, except that 3-methacryloxypropyltrimethoxysilane was replaced with 27.5 g of 8-methacryloxyoctyltrimethoxysilane (KBM-5803: manufactured by Shin-Etsu Chemical Co., Ltd.).

[0327] [Synthesis example 3]

[0328] A 50 mass % HDDA (B-1) dispersion of surface-modified silica particles (A-3) was obtained by the same procedure as in Synthesis Example 1, except that 20.0 g of methacryloyloxymethyltrimethoxysilane (manufactured by Gelest) was used instead of 3-methacryloyloxypropyltrimethoxysilane in step (β) of Synthesis Example 1.

[0329] [2] Evaluation of physical properties of surface-modified silica particles

[0330] The following measurements were performed on the surface-modified silica particles (A-1) to (A-3) obtained in Synthesis Examples 1 to 3. The results are shown in Table 1.

[0331] [Particle size]

[0332] The dispersion was diluted with methanol so that the concentration of the surface-modified silica particles became 1% by mass, and the particle size distribution after 10 minutes of ultrasonic irradiation was measured using a dynamic light scattering / laser Doppler method NANOTRAC particle size distribution measuring apparatus (UPA-EX150: manufactured by Nikkiso Co., Ltd.), and the volume-based median diameter (D50) and D90 / D10 value were calculated.

[0333] [Q 4 / Q]

[0334] Under the following conditions 29 Si-NMR measurement, for the obtained spectrum, calculated the peak area (Q 4 ) to the ratio of the peak area (Q) between -80 and -130 ppm (Q 4 / Q).

[0335] Apparatus: Pulsed Fourier transform nuclear magnetic resonance apparatus (JNM-ECX500II: manufactured by JEOL Ltd.)

[0336] Magnetic field strength: 11.75T

[0337] Cumulative number of times: 10640

[0338] S / N ratio: >5

[0339] Sample tube material: polytetrafluoroethylene

[0340] Solvent: deuterated chloroform

[0341] Reference substance: Tetramethylsilane

[0342] Moderator: Chromium(III) acetylacetonate

[0343] [Content ratio of organic silicon compound]

[0344] The content of the organosilicon compound having a (meth)acryloyl group was calculated as {[the amount of the organosilicon compound having a (meth)acryloyl group added] / [the mass of the sol-gel silica before surface modification]}×100 (mass %).

[0345] [Table 1]

[0346]

[0347] [3] Preparation of photocurable composition

[0348] [Examples 1-1 to 1-15, Comparative Examples 1-1 to 1-7]

[0349] 50 mass % HDDA (B-1) dispersions of the surface-modified silicas (A-1) to (A-3) obtained in Synthesis Examples 1 to 3 and the following components were mixed at the blending ratios (mass %) shown in Tables 2 and 4 to prepare photocurable compositions.

[0350] (C) ingredient: trifunctional (meth)acrylate

[0351] (C-1) Trimethylolpropane ethoxy-modified triacrylate (Miramer M3130: manufactured by MIWON)

[0352] (C-2) Trimethylolpropane triacrylate (Miramer M300: manufactured by MIWON)

[0353] (D) Component: Photoradical initiator

[0354] (D-1) 2-Hydroxy-2-methyl-1-phenyl-propane-1-one (Omnirad 1173: manufactured by IGM RESINS BV)

[0355] (D-2) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (Omnirad TPO-H: manufactured by IGM RESINS BV)

[0356] (E) Component: tetrafunctional or higher polyfunctional (meth)acrylate

[0357] (E-1) Ethoxylated pentaerythritol tetraacrylate (Miramer M4004: manufactured by MIWON)

[0358] (E-2) Dipentaerythritol hexaacrylate (Miramer M600: manufactured by MIWON)

[0359] (F) Ingredient: UV absorber

[0360] (F-1) 2-[2-Hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole (RUVA-93: manufactured by Otsuka Chemical Co., Ltd.)

[0361] (F-2) Hydroxyphenyltriazine-based ultraviolet absorber (Tinuvin 479: manufactured by BASF Japan Ltd.)

[0362] (F-3) An ultraviolet absorber represented by the following structural formula prepared according to Synthesis Example 1 of Japanese Patent No. 6354665

[0363] [Chemistry 7]

[0364]

[0365] [4] Evaluation of physical properties of photocurable compositions

[0366] The photocurable compositions obtained in Examples 1-1 to 1-15 and Comparative Examples 1-1 to 1-7 were evaluated as follows.

[0367] [Kinematic viscosity]

[0368] The kinematic viscosity of the composition at 25° C. was measured using a Cannon-Fenske viscometer (manufactured by Shibata Corporation).

[0369] [5]Manufacture of cured films and coated articles

[0370] [Examples 2-1 to 2-15, Comparative Examples 2-1 to 2-7]

[0371] The compositions obtained in Examples 1-1 to 1-15 and Comparative Examples 1-1 to 1-7 were applied onto a polycarbonate plate (5 mm thick, product name: TAKIRON PC Clear 1600, manufactured by TAKIRON CI Co., Ltd.) using a bar coater #8, and then irradiated in an air atmosphere with a high pressure mercury lamp at 1800 mJ / cm 2 The cured film having a film thickness of 10 μm was prepared by irradiating ultraviolet rays (ultraviolet integrated energy at a wavelength of 300 to 390 nm, measured by using an EYE ultraviolet integrated illuminance meter UVPF-A1 (PD-365): manufactured by Iwasaki Electric Co., Ltd.).

[0372] [6] Evaluation of physical properties of cured films

[0373] The polycarbonate plate having the cured film formed thereon was evaluated for transparency and abrasion resistance as described below. The results are shown in Tables 3 and 5.

[0374] [Transparency]

[0375] The haze (%) was measured using a turbidity meter (NDH2000: manufactured by Nippon Denshoku Industries, Ltd.).

[0376] [Abrasion resistance]

[0377] In accordance with ASTM1044, a wear wheel SC-10F was installed in the Taper wear test, and the haze after 500 revolutions under a load of 500 gf was measured using a haze meter (NDH5000SP: manufactured by Nippon Denshoku Industries Co., Ltd.), and the difference from the value before the wear test (ΔHz, % points) was calculated.

[0378] [Table 2]

[0379]

[0380] [Table 3]

[0381]

[0382] [Table 4]

[0383]

[0384] [Table 5]

[0385]

[0386] *Cannot be measured due to the turbidity of the coating film

[0387] As shown in Table 2, the photocurable compositions of Examples 1-1 to 1-15 satisfying the essential features of the present invention have low viscosity, and as shown in Table 3, the cured films thereof exhibit excellent transparency and abrasion resistance.

[0388] On the other hand, as shown in Table 5, in Comparative Examples 2-1 and 2-2 not containing inorganic particles, the wear resistance was significantly inferior.

[0389] In Comparative Example 2-3 not containing the (C) trifunctional (meth)acrylate, the coating film was turbid and transparency was greatly impaired.

[0390] In Comparative Examples 1-4 to 1-6, in which the trifunctional (meth)acrylate (C) in the composition of Example 1-1 was replaced with a tetrafunctional or higher polyfunctional (meth)acrylate, the viscosity of the composition increased. In Comparative Examples 2-4 to 2-6, as the content of dipentaerythritol hexaacrylate increased, the abrasion resistance deteriorated.

[0391] Furthermore, when the component (A) was excessive as in Comparative Example 1-7, the viscosity of the composition increased, and in Comparative Example 2-7, the transparency was also poor.

Claims

1. A photocurable composition comprising: (A) 1 to 30 parts by mass of surface-modified inorganic particles, which are chemically bonded to at least one of an organosilicon compound represented by the following formula (1), a hydrolyzate thereof and a condensate thereof, and have a volume-based median diameter of 1 to 60 nm, based on 100 parts by mass of the inorganic particles; (B) difunctional (meth)acrylate, (C) trifunctional (meth)acrylate and (D) a photoradical initiator, in, The amount of the component (A) is 10 to 35% by mass, and the total amount of the components (A), (B) and (C) is 70% by mass or more. [Chemistry 1] In the formula, R 1 is a hydrogen atom or a methyl group, R 2 is an alkylene group having 1 to 20 carbon atoms, R 3 are each independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 4 Each independently represents a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, or a halogen atom; and n is an integer of 1 to 3.

2. The photocurable composition according to claim 1, wherein The inorganic particles are silicon dioxide particles.

3. The photocurable composition according to claim 2, wherein The value of D90 / D10 in the volume-based particle size distribution of the surface-modified inorganic particles is 3.2 or less.

4. The photocurable composition according to claim 2 or 3, wherein The surface-modified inorganic particles are 29 The peak area (Q) of -105 to -130 ppm in the Si-NMR spectrum 4 ) to the ratio of the peak area (Q) between -80 and -130 ppm (Q 4 Particles obtained by surface-modifying sol-gel silica particles having a / Q) of 0.8 or less.

5. The photocurable composition according to any one of claims 1 to 4, wherein The surface-modified inorganic particles are particles to which one or more selected from the group consisting of a silane compound represented by the following formula (5) and a disilazane compound represented by the following formula (6) are further chemically bonded. R 5 3SiY(5) R 5 3Si-NH-SiR 5 3(6) In the formula, R 5 Each of them is independently an alkyl group having 1 to 8 carbon atoms, and each of Y is independently a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, an acyloxy group having 1 to 6 carbon atoms, an amino group or a halogen atom.

6. The photocurable composition according to any one of claims 1 to 5, wherein The content of the volatile organic solvent is less than 10% by mass based on the entire composition.

7. The photocurable composition according to any one of claims 1 to 6, which has a kinematic viscosity at 25°C of 100 mm 2 / s or less. 8 . A cured product formed by curing the photocurable composition according to claim 1 .

9. An article coated with the cured product according to claim 8.

Citation Information

Patent Citations

  • Sampler for lower part of shaft of blast furnace

    JP1986056214A

  • X-ray spectroscopic element

    JP1986089547A

  • Automatic changing processing machine for reservation ticket

    JP1988054665A

  • Composition for hard coat

    JP2008150484A

  • Photocurable resin composition and article having cured coating

    JP2010189620A